Psychological capital and well-being among Malaysian teacher - Burhanuddin, Nur Aimi Nasuha; Ahmad, Nor Aniza (Training Center for Social Science and Education, 2018)
This study through educational narratives aims to explore the well being of teachers in Malaysia school as well as the use of psychological capital (PsyCap) in this profession. It has been well documented in previous research that teaching as a high-stress profession that affect teacher’s well being and performance at work and to a greater consequence result to teacher’s turnover. While some teachers face those circumstances, there are those who are able to successfully overcome those challenges and retain positive commitment to the work. This could be very well explained by the model of Psychological Capital that underlies by four core constructs which is optimism; hope; self-efficacy; and resilience. Previous study shows that these constructs have positive relationship with teacher’s well being (Stajkovic & Luthans, 1998). Focus has been given on this issue due to the fact that through the introduction of Malaysia Education Blueprint 2013-2025, Education Ministry of Malaysia is serious in assuring teaching to become the career of choice. Hence, teacher’s welfare should be taken in consideration. The studies on psychological capital are mostly done in quantitative method and only limited number of studies was done qualitatively. This study attempts to contribute to the literature by adopting qualitative research paradigm. This study may be used to increase the understanding on which components of PsyCap teachers have and to what extent they give importance to the construct.